Factors influencing cervical cancer screening in a Kenyan Health Facility: a mixed qualitative and quantitative study - Njuguna, E.; Ilovi, S.; Muiruri, P.; Mutai, K.; Kinuthia, J.; Njoroge, P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the commonest cause of cancer-related morbidity and mortality among women in developing countries in sub-Saharan Africa. Screening for cervical cancer among HIV infected women is crucial as they are more at risk of developing the disease and progressing faster once infected with Human Papilloma Virus (HPV). Methods: We aimed to determine the factors affecting the utilization of cervical cancer screening among HIV infected women above 18 years of age at Kenyatta National Hospital by conducting a cross-sectional mixed quantitative and qualitative methods study. Descriptive and inferential analysis was carried out on quantitative data to determine significant associations with cervical cancer utilization. Qualitative data were analyzed after coding for significant clauses and transcribing to determine themes arising. Results: Three hundred and twenty eight of the total 387 women enrolled reported they had been advised by their health providers to go for screening. However, only 179 (46%) reported cervical cancer screening. Women were more likely to report cervical cancer screening if recommendation by a staff was made (p <0.001), and prior to joining KNH CCC (p <0.001). Qualitatively the main barrier to screening included fear of screening due to concerns about excessive pain or bleeding, lack of proper communication on screening procedures and long waiting time Conclusions: The utilization of cervical cancer screening services was low despite high rates of health care recommendation. The women were more likely to utilize the service if recommendation from the health care worker was made, and if they had ever screened before.